2017
DOI: 10.21595/jve.2017.17931
|View full text |Cite
|
Sign up to set email alerts
|

Image processing in detection of knee joints injuries based on MRI images

Abstract: This paper presents image processing methods for visualization and classification of medial meniscus tears. The first method uses watershed with a threshold segmentation approach. The algorithm was tested on a number of images of the knee obtained with a use of the magnetic resonance imaging technique (MR). Images of the knee were collected from healthy subjects and patients with a clinically diagnosed meniscal pathology. Then, watershed technique was compared with other popular methods of image segmentation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…The results show the superiority of the watershed segmentation from the point of view of effectiveness and better distinguishing of some irregularities. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show the superiority of the watershed segmentation from the point of view of effectiveness and better distinguishing of some irregularities. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that watershed segmentation has the potential to be used as a screening method for meniscal injuries and diseases, with the aim of improving care. [ 17 18 19 20 ] We could not find an article that has used this algorithm for the detection of Baker's cyst in MRI. Moreover, due to more accuracy detection of lesions and delineation lymphomas, a nominated algorithm was performed in mammography and computed tomography.…”
Section: Discussionmentioning
confidence: 99%